Contributions of Health Professions Students to Health System Needs During the COVID-19 Pandemic: Potential Strategies and Process for U.S. Medical Schools. (November 2020) - Long, Nathaniel; Wolpaw, Daniel R.; Boothe, David; Caldwell, Catherine; Dillon, Peter; Gottshall, Lauren; Koetter, Paige; Pooshpas, Pardis; Wolpaw, Terry; Gonzalo, Jed D.
Abstract : The COVID-19 pandemic poses an unprecedented challenge to U.S. health systems, particularly academic health centers (AHCs) that lead in providing advanced clinical care and medical education. No phase of AHC efforts is untouched by the crisis, and medical schools, prioritizing learner welfare, are in the throes of adjusting to suspended clinical activities and virtual classrooms. While health professions students are currently limited in their contributions to direct clinical care, they remain the same smart, innovative, and motivated individuals who chose a career in health care and who are passionate about contributing to the needs of people in troubled times. The groundwork for operationalizing their commitment has already been established through the identification of value-added, participatory roles that support learning and professional development in health systems science (HSS) and clinical skills. This pandemic, with rapidly expanding workforce and patient care needs, has prompted a new look at how students can contribute. At the Penn State College of Medicine, staff and student leaders formed the COVID-19 Response Team to prioritize and align student work with health system needs. Starting in mid-March 2020, the authors used qualitative methods and content analysis of data collated from several sources to identify 4 categories for student contributions: the community, the health care delivery system, the workforce, and the medical school. The authors describe a nimble coproduction process that brings together all stakeholders to facilitate work. The learning agenda for these roles maps to HSS competencies, an evolving requirement for all students. The COVID-19 pandemic has provided a unique opportunity to harness the capability of students to improve health. Other AHCs may find this operational framework useful both during the COVID-19 pandemic and as a blueprint for responding to future challenges that disrupt systems of education and health care in the United States.